Effect of Plyometric and Weight Training on Explosive Power and Muscle Mass in Taekwondo Athletes In Semarang City - Dhuha, Ahad Agafian; Yogaswara, Andre; Muhibbi, Muhammad; Widodo, Agung; Abubakar, Sayid Fariz Bin Seh; Sinaga, David Hasian Barutu (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2025)
The purpose of this study was to determine the effects of plyometric and weight training on explosive power and muscle mass, and to determine which method was more effective at increasing both. Taekwondo is a sport that requires considerable explosive power and muscle mass, so training is needed to improve these components. Explosive power enables athletes to attack quickly and forcefully, while muscle mass provides ideal proportions. The research method used was a quasi-experimental pre-test-post-test two-group design with treatment consisting of plyometric and weight training. The research instruments were the standing board jump and body analysis. The research sample consisted of 15 taekwondo athletes from Semarang. The results showed that plyometric and weight training exercises increased explosive power and muscle mass. Still, plyometric training was more effective at increasing explosive power, and weight training was more effective at increasing muscle mass. The paired sample t-test results show that all variables have a significance value (Sig. 2-tailed) of 0.000, which is less than 0.05. This indicates a significant difference between the pre-test and posttest values across all groups. This study is expected to serve as a reference for the development of training programs to increase explosive power and muscle mass.